Enhancing terrestrial solar power using orbiting solar reflectors. (June 2022) - Çelik, Onur; Viale, Andrea; Oderinwale, Temitayo; Sulbhewar, Litesh; McInnes, Colin R.
Abstract: The delivery of global clean energy services represents a key challenge for the 21st century. In order to deliver such services, it is clear that large-scale solar power farms will continue to grow both in number and size. In principle, ultralight membrane orbiting solar reflectors can illuminate large-scale solar power farms during the critical dawn/dusk hours of the day, enhancing the utility of terrestrial solar power. The key advantage is that only a relatively modest mass needs to be delivered to Earth orbit. This paper discusses the technical challenges associated with the development, deployment and operation of such a space-based energy service. Business development models are discussed along with regulatory issues and finally an integrated technology demonstration roadmap is presented. Highlights: Orbiting solar reflectors offer a timely opportunity to enhance terrestrial solar energy output. Repeat ground track Sun-synchronous orbits are proposed for daily global access to solar power farms. A double-boom configuration is proposed with CMGs attached, the booms null gravity gradient torques by equalizing inertias. A hexagonal reflector configuration fabricated from triangular units is proposed for standardization and modularity. National, commercial and hybrid models are proposed; economic analysis suggests feasibility with falling launch costs.